Antibacterial Activity of the Red Algae Eucheuma cottonii Extract from Tanjung Coast, Sumenep Madura - Andriani, Zulli; Fasya, Ahmad Ghanaim; Hanapi, Ahmad (ALCHEMY, 2015)
AbstractRed alge Euchema cottonii is one of the biological source that has benefits. The aim of this study is to determine the effectiveness of antibacterial red algae Eucheuma cottonii extract. Isolation of active compounds was performed by maceration method using methanol. The methanol extract was hydrolyzed using HCl 2 N and partitioned by ethyl acetate, chloroform, petroleum ether and n-hexane solvents. The antibacterial assessment was determined using disc diffusion method againts bacteria Staphylococcus aureus and Escherichia coli. Identification of active compound was conducted by reagents test. The results showed that the best solvent to extract algae was methanol with 20.7% rendemen. The methanol extract 4% gives the highest inhibition at concentrations was 7.85 mm; followed by n-hexane and chloroform were 1.0 and 0.6 mm. However, bath ethyl acetate and petroleum ether extract depicted no inhibition zone. The identification test showed the presence of flavonoids, triterpenoids, steroids and alkaloids in the methanol extract. The extract of n-hexane contained triterpenoids and alkaloids, while the chloroform extract contained flavonoids, triterpenoids and alkaloids.Â Keywords:Â  Euchema cottonii, antibacterial, disc diffusion